Effect of induced diabetes mellitus on alveolar bone loss after 30 days of ligature-induced periodontal disease - Gomes, Débora Aline Silva; Spolidório, Denise Madalena Palomari [UNESP]; Pepato, Maria Teresa; Zuza, Elizangela Partata; de Toledo, Benedicto Egbert Corrêa; Gonçalves, Andréa [UNESP]; Spolidório, Luis Carlos [UNESP]; Pires, Juliana Rico (My University, 2009)
Several studies have shown that diabetics are more susceptible to the development of severe periodontal disease. Currently, the use of animal models can be considered a feasible alternative in radiographic assessments of these two pathologies. The purpose of this radiographic study was to evaluate the effect of induced diabetes mellitus on alveolar bone loss after 30 days of ligature-induced periodontal disease. Sixty-four Wistar rats were randomly distributed into four experimental groups. Diabetes was induced in Groups II and IV, while periodontal disease was induced in Groups III and IV; Group I was used as control. In order to perform the radiographic assessment of the specimens, the rats were killed on the 3rd and 30th days of the study. Radiographic measurements were assessed with ANOVA and Tukey's test to determine statistically significant differences (p < 0.05). It was observed that Groups III and IV featured greater bone loss when compared to Groups I and II. Only the diabetic group with periodontal disease (Group IV) featured statistically significant greater bone loss when compared to the other groups. These results suggested that the alveolar bone loss resulting from the periodontal disease installation is greater when associated to the diabetes mellitus.
Keywords: streptozocin; animal; blood; cephalometry; comparative study; experimental diabetes mellitus; instrumentation; ligation; male; osteolysis; periodontal disease; radiography; randomization; rat; time; tooth radiography; Wistar rat; Alveolar Bone Loss; Animals; Cephalometry; Diabetes Mellitus, Experimental; Furcation Defects; Ligation; Male; Periodontal Diseases; Radiography, Dental, Digital; Random Allocation; Rats; Rats, Wistar; Streptozocin; Time Factors